PENYERAPAN LOGAM BERAT SECARA BIOKIMIAWI OLEH BAKTERI GRAM POSITIF DAN GRAM NEGATIF: A MINI RIVIEW - Dilo Jhosea Luciano Eduardo; Rudi Kartika; Ripaldy Apriansya; Shaparuddin Nur Arifullah; Muhammad Adhitya Rizkirullah (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2025)
Scenedesmus sp. is a freshwater green alga that functions as an ionic biosorbent and can also be a bioindicator for water contaminated with hexavalent chromium Cr(VI) ion. This study aimed to observe the growth of Scenedesmus sp. exposed to Cr(VI) ion at various concentrations and analyze the remaining Cr(VI) ion that did not undergo biosorption by microalgae. This research was conducted on Scenedesmus sp. microalgae growth media using five bioreactors, each with a different Cr(VI) ion exposure concentration. The remaining ion in the growth media was analyzed for its concentration with an ultraviolet-visible spectrophotometer at time variations with an interval of two days. Maximum biosorption with exposure to Cr(VI) occurred at a concentration of 1.0 ppm on day 12 of 99.93%. At concentrations of 5.0 ppm and 7.0 ppm, microalgae growth was very poor, indicating the medium was toxic. Keywords: Biosorption, Hexavalent Chromium, Scenedesmus sp, Toxicity